Web-Based Realtime Course Platform With Integrated Live Coding Interface - Chenartha, Reinald; Safitri, Cutifa (IT for Society, 2024)
This paper explores an innovative technologicalapproach to a programming education platform. The platformaims to enhance the learning experience by integrating web-based resources with real-time video communication and livecoding. Utilizing a peer-to-peer connection framework, thismethod facilitates efficient and direct communication betweeninstructors and learners, optimizing performance and reducinglatency. The primary goal is to create a dynamic andcollaborative learning environment. Through the integration ofpeer-to-peer video chat and an Integrated DevelopmentEnvironment (IDE), the platform aims to improve real-timecommunication, code reviews, and interactive problem-solving,providing learners with a profound programming learningexperience.